Impact of altered cell wall composition on saccharification efficiency in stem tissue of Arabidopsis RABA GTPase-deficient knockout mutants - Lunn, Daniel; Ibbett, Roger; Tucker, Gregory A.; Lycett, Grantley W. (Springer, 2015)
Use of biomass for second-generation biofuel production is severely hindered by the inherent recalcitrance of the plant cell wall to digestion. Trafficking is crucial for compartmentalisation within the cell. This process is partly regulated by small Rab GTPase proteins. In particular, control of trafficking to the cell wall is regulated through the RABA clade. Manipulation of this regulatory system offers tantalising opportunities for manipulation of cell wall composition and hence recalcitrance. Trafficking-defective rabA mutants have already been shown to impact cell wall composition. To study the impacts of these mutants on cell wall digestion, we developed a saccharification process for Arabidopsis based on the hot water method. We then showed that following pre-treatment, stems from the T-DNA knockouts of the three RABA4 genes expressed in Arabidopsis stem show an increased sugar release on saccharification. These rabA4 mutants have been shown to impact the “hemicellulose-rich” fraction during cell wall fractionation. Furthermore, we go on to show that these mutant lines also show increased sugar release when subjected to saccharification without pre-treatment. Finally, we used X-ray diffraction to show that rabA4 mutants had no impact on cellulose crystallinity, thus supporting the hypothesis that the increases in saccharification were not due to alterations of the cellulose microfibrils but were a direct effect of reduced hemicellulose levels. We also present data to show that the growth characteristics of these plants were unaffected. The data obtained from these lines are most easily explained by the reported alteration in hemicellulose increasing pre-treatment efficiency.